2020
DOI: 10.1029/2019ja027297
|View full text |Cite
|
Sign up to set email alerts
|

SAMI3 Simulations of Ionospheric Metallic Layers at Arecibo

Abstract: The Naval Research Laboratory Sami3 is Also a Model of the Ionosphere (SAMI3) ionosphere/plasmasphere code is used to examine the physics of metallic layers at altitudes from 80 to 160 km. Results are presented near the simulated location of the Arecibo observatory (18°N, 66°W). We find that simulations, using winds from the empirical horizontal wind model, produce layers consistent with those observed at Arecibo. Specifically, we find upper semidiurnal and lower diurnal traces similar to those identified in p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…1a. This numerical result is similar to previous E s layer simulation results (Carter and Forbes 1999;Krall et al 2020;Mathews and Bekeny 1979). In Case A, the fundamental structure of the E s layer is reproduced; the E s layers are created by the semidiurnal tide, descend with its vertical wind shears, and remain around 100 km.…”
Section: Model Descriptionsupporting
confidence: 88%
See 3 more Smart Citations
“…1a. This numerical result is similar to previous E s layer simulation results (Carter and Forbes 1999;Krall et al 2020;Mathews and Bekeny 1979). In Case A, the fundamental structure of the E s layer is reproduced; the E s layers are created by the semidiurnal tide, descend with its vertical wind shears, and remain around 100 km.…”
Section: Model Descriptionsupporting
confidence: 88%
“…2c, but the range of altitude is from 85 km to 130 km altitude because the E s layers in Fig. 2c appear below 130 km and the vertical ion velocity above 130 km is mostly controlled by the meridional winds that is same as the previous numerical results (Carter and Forbes 1999;Krall et al 2020). Positive values in Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is believed that these structures are caused mainly due to additional wind shears produced by the atmospheric gravity waves (e.g., Roddy et al, 2007;Rowe, 1974). Till date, many numerical studies of MILs have been conducted by a variety of global and regional ionospheric models (e.g., Carrasco et al, 2007;Carter & Forbes, 1999;Chu & Yu, 2017;Huba et al, 2019;Krall et al, 2020;Shinagawa et al, 2017). Huba et al (2019) and Krall et al (2020) have performed SAMI3 simulations with Horizontal Wind Model (HWM14) (Drob et al, 2015), and have shown 3-D structures of the MILs for the first time.…”
mentioning
confidence: 99%